2006
DOI: 10.1158/0008-5472.can-05-0470
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin-C Stimulates Glioma Cell Invasion through Matrix Metalloproteinase-12

Abstract: The capacity of glioma cells to invade extensively within the central nervous system is a major cause of the high morbidity rate of primary malignant brain tumors. Glioma cell invasion involves the attachment of tumor cells to extracellular matrix (ECM), degradation of ECM components, and subsequent penetration into adjacent brain structures. These processes are accomplished in part by matrix metalloproteinases (MMP) within a three-dimensional milieu of the brain parenchyma. As the majority of studies have use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 49 publications
(65 reference statements)
2
108
0
Order By: Relevance
“…Tenascin-C is strongly implicated in mediating the invasive behavior of glioma cells, and early studies showed that tenascin-C stimulated fibronectinmediated cell migration (Deryugina and Bourdon 1996). Similar observations have been made by several different research groups (Hirata et al 2009;Sivasankaran et al 2009); in one report, this migration was found to be dependent on the induction of metalloproteinase-12 (Sarkar et al 2006). The connection between tenascin-C expression and invasion is, however, not restricted to brain tumors.…”
Section: Tenascins In Cell Migration Cancer Cell Invasion and Metassupporting
confidence: 84%
“…Tenascin-C is strongly implicated in mediating the invasive behavior of glioma cells, and early studies showed that tenascin-C stimulated fibronectinmediated cell migration (Deryugina and Bourdon 1996). Similar observations have been made by several different research groups (Hirata et al 2009;Sivasankaran et al 2009); in one report, this migration was found to be dependent on the induction of metalloproteinase-12 (Sarkar et al 2006). The connection between tenascin-C expression and invasion is, however, not restricted to brain tumors.…”
Section: Tenascins In Cell Migration Cancer Cell Invasion and Metassupporting
confidence: 84%
“…Excessive production of MMPs could increase the invasion and mobility of tumor cells. A recent study has shown that MMP-12 is overexpresssed in various human cancers, e.g., epithelial ovarian carcinoma (Li et al, 2009), prostate cancer (Nabha et al, 2008), endometrial adenocarcinoma (Yang et al, 2007a), glioma cell (Sarkar et al, 2006), non-small cell lung cancer (Hofmann et al, 2005), oral verrucous and squamous cell cancer (Impola et al, 2004) and squamous cell carcinoma (Kerkela et al, 2002). In addition, FUT4 is mainly expressed in leukocytes and some epithelial cells (Allahverdian et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-14 activates MMP-2 by cleaving its pro-peptide (54,55). Furthermore, MMP-3, -7, -12, -13, -16, -19, and -26 are also highly expressed and mostly associated with enhanced glioma invasion (56)(57)(58)(59)(60)(61)(62)(63). MMPs are inhibited by the four tissue inhibitors of metalloproteinases (TIMP), TIMP-1-4.…”
Section: Matrix-metalloproteinasesmentioning
confidence: 99%